Direct and Indirect Effects of Case Complexity, Guilty Pleas, and Offender Characteristics on Sentencing for Offenders Convicted of a White-Collar Offense Prior to Sentencing Guidelines - Albonetti, Celesta Ann (Journal of quantitative criminology, 1998)
Previous research on the punishment of offenders convicted of a white-collar offense estimated models that specify only direct effects of defendant characteristics, offense-related variables, and guilty pleas on sentence severity. Drawing from conflict or labeling theories, much of this research focused on the effects of offender's socioeconomic status on sentence outcomes. Findings from this research are inconsistent about the relationship between defendant characteristics and sentence severity. These studies overlook how differences in case complexity of white-collar offense and guilty pleas may intervene in the relationship between offender characteristics and sentence outcomes. This study seeks to contribute to an understanding of federal sentencing prior to the federal sentencing guidelines by testing a legal-bureaucratic theory of sentencing that hypothesizes an interplay between case complexity, guilty pleas and length of imprisonment. This interplay reflects the interface between the legal ramifications of pleading guilty, prosecutorial interests in efficiency and finality of case disposition in complex white-collar cases, and sentence severity. Using structural equation modeling, a four-equation model of sentencing that specifies case complexity and guilty pleas as intervening variables in the relationship between offender characteristics and length of imprisonment is estimated. Several findings are noteworthy. First, the hypothesized interplay between case complexity, guilty pleas, and sentence severity is supported. Second, the effect of offender's educational attainment on sentence severity is indirect via case complexity and guilty pleas. Third, offender's race and gender effect length of imprisonment both directly and indirectly through the intervening effect of case complexity and guilty pleas. These findings indicate the need to specify sentencing models that consider the direct and indirect effects of offender characteristics, offense characteristics, and guilty pleas on judicial discretion at sentencing.